"Good morning, Twitter! What are you doing today to support the voice of people with #disability?": disability and digital organizing. Issue 3 (3rd July 2021) - Sarkar, Tanushree; Forber-Pratt, Anjali J.; Hanebutt, Rachel; Cohen, Mae
ABSTRACT: Understanding Twitter by individuals and organizations to raise awareness and give voice to the disability community provides important insight into digital discourse around disability. This study examines #disability tweets shared during National Disability Employment Awareness Month in October 2018. Sourced and cleaned, English language tweets ( n = 12, 963) were analyzed through a mixed-methods approach. As the title of this paper, a tweet from our dataset, suggests, Twitter discourse reflects disability activism and culture as it exists globally. This work highlights important methodological considerations for differentiating the ways individuals and organizations utilize Twitter and highlights the importance of qualitative analysis in this regard.